2001
DOI: 10.1159/000050403
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Birth Injuries in Term Newborn Infants

Abstract: While cranial birth injuries in term infants are well recognized, to date, only small case series have been described. In an attempt to further define the spectrum of cranial birth injuries, we analyzed 41 consecutive cranial birth injuries at our institution over the period 1991–1998. The most common clinical presentations were apnea (39%) and seizures (37%). Average Apgar scores were 5.7 at 1 min and 7.3 at 5 min; 54% of infants had abnormally low Apgar scores at 1 min and 31% had abnormally low scores at 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 15 publications
2
26
0
2
Order By: Relevance
“…SDH is known to be common in infants with cranial birth injury [13], but there is an increasing awareness that it is also common in asymptomatic neonates, with estimates of incidence ranging from 8% [16] to 46% [14]. It is generally considered that birthrelated SDH is reabsorbed by 1 month of age, based on imaging studies [25].…”
Section: Discussionmentioning
confidence: 99%
“…SDH is known to be common in infants with cranial birth injury [13], but there is an increasing awareness that it is also common in asymptomatic neonates, with estimates of incidence ranging from 8% [16] to 46% [14]. It is generally considered that birthrelated SDH is reabsorbed by 1 month of age, based on imaging studies [25].…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanisms for SDH have included tears of the falx and tentorium or bridging cortical veins secondary to stretching, 11 difficult delivery, 26,27 or abnormal labor. 19 One suggested mechanism of hemorrhage after vaginal delivery is that increased circumferential pressure and squeezing of the head in the birthing canal result in overlap at the sutures, mechanical compression, and shearing of the bridging veins during delivery, resulting in SDH.…”
Section: Discussionmentioning
confidence: 99%
“…29, 30 Towner et al 19 suggested that abnormal labor was a common risk factor for hemorrhage in infants, after a retrospective review of deliveries in nulliparous women demonstrated a low incidence of intracranial hemorrhage. Pollina et al 27 suggested that the method of assisted delivery rather than the urgency of the delivery or dysfunctional labor is a more important variable in cranial birth injuries. Although all types of intracranial hemorrhage were more common in vacuum extraction, not all term neonate SDHs can be explained by circumferential head squeeze and overlapping sutures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VE is reported to be associated with rare but severe cerebral complications [9], although study limitations have been small sample size and retrospective design [9,10], composite outcomes [11], mixed term and preterm deliveries [12,13], no comparisons of rates of intracranial complications in vacuum extraction and caesarean section (CS) deliveries [9,13]. In addition, few studies have investigated the association between VE and neonatal encephalopathy and the results are contradictive [13,14].…”
Section: Introductionmentioning
confidence: 99%